Flexural Properties of Steel-Bamboo Composite Slabs in Different Connection Methods - Hui Zhong; Qifeng Shan; Jialiang Zhang; Xiaocun Zhang; Yushun Li (Advances in Civil Engineering)
This paper presents a study aimed to estimate the flexural performance of profiled steel sheet-bamboo plywood composite slabs as a first step to evaluate its potential application as structural components. Nine specimens were tested to investigate the stability of steel-bamboo composite structure. According to different connection methods, three types of composite slabs were discussed, including pure bonding slabs (PBSs), composite bonding slabs (CBSs), and reinforced composite bonding slabs (RCBS). The result showed that specimens employed multiple composite methods (RCBS) exhibited excellent flexural bearing capacity and stiffness compared with PBS. The increase of bamboo plywood thickness could improve bearing capacity and flexural stiffness of composite slabs, while the reduction of screw spacing could enhance the bearing capacity and ductility of composite slabs. The RCBS, which can provide higher bearing capacity and stiffness and possess excellent deformation capability, are well worth of research and practical application.